2021
DOI: 10.3390/jcm10143089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Utility of Assaying FGF-23, Klotho Protein, Osteocalcin, NTX, and Sclerostin in Patients with Primary Hyperparathyroidism

Abstract: The purpose of this study was to assess the clinical usefulness of assaying the fibroblast growth factor (FGF-23), Klotho, osteocalcin, N-terminal telopeptide of type I collagen (NTX), and sclerostin levels in patients with primary hyperparathyroidism (PHPT) as markers of bone damage as well as for surgical treatment success. Seventeen patients with hypercalcemic PHPT and normal kidney function were studied. In all patients, PTH (parathormone), serum calcium, and creatinine were performed before and six months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Several studies have failed to demonstrate significantly higher FGF23 levels in PHPT patients with normal renal function than in healthy controls as well as any change in FGF23 concentration after parathyroidectomy (12, 16-18). In contrast, other studies showed that increased FGF23 levels observed in PHPT significantly decreased after successful parathyroidectomy (19)(20)(21)(22). Furthermore, to our knowledge, FGF23 levels have never been previously evaluated in the increasingly recognized NPHPT phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have failed to demonstrate significantly higher FGF23 levels in PHPT patients with normal renal function than in healthy controls as well as any change in FGF23 concentration after parathyroidectomy (12, 16-18). In contrast, other studies showed that increased FGF23 levels observed in PHPT significantly decreased after successful parathyroidectomy (19)(20)(21)(22). Furthermore, to our knowledge, FGF23 levels have never been previously evaluated in the increasingly recognized NPHPT phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…Osteocalcin regulates the regulation of bone resorption, but also the mineralization of the matrix and differentiation of osteoblasts, a mechanism that maintains the normal mineralization of bone, inhibits the mineralization of cartilage and the abnormal hydroxyapatite crystal formation of bone. A study from Poland found that the osteocalcin levels of 17 PHPT patients returned to normal at six months after surgery ( 27 ). In our study, although osteocalcin did not fall into normal ranges in all patients, the median level of osteocalcin significantly decreased from 35 ng/mL to 22 ng/mL, indicating the improvement of bone turnover status.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that 1.25(OH) 2 vitamin D levels correlated with FGF-23 levels both preoperatively and postoperatively, although they could not find any other significant relationship with calcium, phosphate, and PTH. Another recent study has assessed FGF-23 in PHPT patients [ 20 ]. Seventeen hypercalcemic PHPT patients were evaluated before parathyroidectomy and 6 months after surgery.…”
Section: Phosphate In Primary Hyperparathyroidismmentioning
confidence: 99%